P284 THE RIGHT HEART ADAPTATS TO EXERCISE MORE EFFICIENTLY IN PULMONARY ARTERIAL HYPERTENSION THAN IN PULMONARY HYPERTENSION DUE TO HEART FAILURE WITH PRESERVED EJECTION FRACTION. (18th May 2022) - Baratto, C; Caravita, S; Dewachter, C; Faini, A; Villella, F; Perego, G; Muraru, D; Badano, L; Parati, G; Vachiéry, J
Abstract: Background: Right heart failure (RHF) represents the final step of distinct diseases, differently involving the pulmonary circulation, such as pulmonary arterial hypertension (PAH) and pulmonary hypertension (PH) due to heart failure with preserved ejection fraction (HFpEF). Exercise may unmask right heart maladaptation as a sign of RHF, but cut–offs for right atrial pressure (RAP) rise during exercise remain to be defined. We hypothesized that PH–HFpEF may present with worse right heart adaptation to exercise than PAH due to increased chamber stiffness and dysfunctional preload. Aim: We sought to describe the behavior of RAP during exercise in PAH and in PH–HFpEF, and the mechanisms underlying right heart maladaptation. Methods: We performed a retrospective analysis of data (2007–2021) obtained from patients with either PAH or PH–HFpEF who underwent a right heart catheterization at rest and during exercise. Right heart adaptation to exercise was described using either absolute or cardiac output (CO)–normalized RAP increase during exercise (RAP/CO slope). Patients with non–cardiac dyspnea (NCD) served to define RAP limits of normality. Estimated stressed blood volume (eSBV), as a measure of effective preload, was computed based on hemodynamics using a commercially–available software. Results: Ninety–four patients were included (32 PH–HFpEF, 32 PAH and 30 NCD). The upper limit of normal for absolute peak RAP and RAP/CO slope were 12 mmHg and 1.55 mmHg/L/min. Compared with PH–HFpEF, PAH patients showed higher systolic, diastolic and mean pulmonary artery pressure (PAP) as well as higher indices of right ventricular afterload both at rest and during exercise, but lower filling pressures and similar CO (Figure 1 ).In particular, PH–HFpEF had higher peak RAP and higher RAP/CO slope than PAH (Figure 1, 2 ). Additionally, 78% and 91% of PH–HFpEF, as compared with 47% and 44% of PAH had a RAP/CO slope and a peak RAP above normal, respectively (p < 0.001). PH–HFpEF presented with higher increase in eSBV, and higher peak eSBV values than PAH (p < 0.05), despite similar resting levels. RAP/eSBV slope was upward shifted (at a given effective preload, RAP was higher) while CO/eSBV slope was flatter (at a given effective preload, CO was lower) in PH–HFpEF as compared with PAH (Figure 3 ). Conclusions: PH–HFpEF display worse right heart maladaptation to exercise than PAH, likely due to a combination of increased right heart stiffness and a more exhausted Frank–Starling reserve.